(3bUjOI GdHSGeI GdcHQis - (3eMeO Hf YHOhfs
(3ChdgG (B:s
(3GdOgQ jaLY HYO GdYjf HGdCKQ (B*** (3aeG GdHcG Ydi GdCTHGM hGdUhQ , CfgGc CfgGc dG Bdhc ehYXI (B*** (3Yf fhMI Hjf fGH GddjK hGdXaQs
(3BNQgG (B:s
(3SjGQI aj CbGUj GdCQV bGWYI (B*** (3TbGTbG gOQJ aj GdHOh hGdMVQ (B*** (3hWGYI GdCeQ aj GdCdHGH bGVjI (B*** (3ef GdeSGeY eG de jbV ef hWQs
(3aj BNQg HOGjI bUjOI UGQe GdOjf EHQGgje Hf GdgGOj Hf GdhRjQ eYGQVG dGHf YHOhfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdCOHs